The Cashless Economy in Vietnam - The Situation and Policy Implications - Ha, Hoang (Journal of Reviews on Global Economics, 2020)
A cashless economy is one where purchases and transactions are done mainly by electronic means and seldom by cash (Ejiofor and Rasaki 2012). Vietnam has now joined the Better Than Cash Alliance (Betterthancash.org 2017) and the ambitious goal of the government is in 2020, the proportion of cash on total payment means is lower than 10% (Vu 2018). Non-cash payment - a pillar of the cashless economy - has become a very popular means of payment in the world and is expanded used commonly in Vietnam. Through researching payment via mobile banking (MB), we surveyed of over 140 people in Da Nang city to find out demographic characteristics, the most used cashless payment features, as well as the ratio of cashless payment to total spending. The situation was evaluated and several important policy implications were proposed for Vietnamese government.